Microscopic Colitis. Common Features and Differences - Galina M. Mogil’naya; Vladimir M. Durleshter; Vera L. Mogil’naya; Lida K. Kovaleva; Lyudmila G. Dryaeva (Кубанский научный медицинский вестник)
Aim. To study the morpho-molecular mechanisms underlying the formation of microscopic colitis (MC), as well as to identify features of its two forms – collagenous and lymphocytic.Material and methods. We studied biopsy samples from 23 patients exhibiting a clinical picture of irritable bowel syndrome; the material was obtained at the Endoscopic Department of the Region Clinic Hospital No. 2. The material was sampled from the five zones of the large intestine specified in the guidelines (Clinical Guidelines — Diagnosis and treatment of patients with digestive diseases, Appendix No. 3). The material was fixed in 10 % formalin, processed and embedded in paraffin. Sections were stained with hematoxylin and eosin (according to Mallory and Masson), as well as with picrosirius red, followed by the examination of these sections in polarised light. The immunohistochemical study was performed in line with the guidelines using monoclonal antibodies. Abcam antibodies (England) were used to detect type I and type III collagen; Cell Marque antibodies to CD4+ T and CD8+ T-lymphocytes (USA) were used to characterise lymphocytes.Results. It has been established that fi broblasts in the lamina propria play a key role in the pathogenesis of collagenous MC. This cell population synthesises extracellular matrix and forms layers of collagen fibres in the area under the surface epithelium. Pericryptal fibroblasts are also activated. Their differentiation occurs simultaneously with the migration of epithelial cells to the surface of the crypts with a possible change in their cellular composition. Intercryptal fi broblasts provide an increase in the synthesis rate of type III collagen. In the case of lymphocytic colitis, the pathogenetic mechanism is based on the relationship between lymphocytes and the cells in the lamina propria. The outcome is determined by the type of activated lymphocytes. CD8+ lymphocytes infiltrate the epithelial lining, causing a reaction to the luminal component, whereas CD4+ lymphocytes act as helpers and populate the lamina propria in the area under the epithelium.Conclusion. The pathogenesis of collagenous MC is based on the mechanism exhibited by the fibroblasts in the colon lamina propria, whereas the pathogenesis of lymphocytic colitis is determined by the dynamics of CD4+ T and CD8+ T-lymphocyte subpopulations.